Guided Endodontic Approach in Teeth with Pulp Canal Obliteration and Previous Iatrogenic Deviation: A Case Series - Braga Diniz, JÃºlia MourÃ£o; Diniz Oliveira, Henrique FranÃ§a; Pinto Coelho, Rodrigo Carvalho; Manzi, FlÃ¡vio; Evangelista Silva , Fernanda; Ribeiro Sobrinho, AntÃ´nio Paulino; Machado, VinÃcius Carvalho; Tavares, Warley Luciano Fonseca (Iranian Endodontic Journal, 2022)
Pulp canal obliteration (PCO) is a challenging clinical scenario in which canals must be located in progressively narrowing roots. Recently, proof of concept papers have, in parallel, introduced the combination of cone-beam computed tomography and surface scans for the construction of guides to pilot the negotiation and preparation of partially or completely obliterated pulp chambers and canals in anterior and posterior teeth. Authors’ purpose is to describe the treatment approach for teeth with PCO and previous iatrogenic deviation using guided endodontic technique. The clinical cases reported here show that technological evolutions should make guided endodontic procedures more widespread because their execution is relatively fast and safe even in the cases of root canal deviation. Treatment of teeth with pulp canal obliteration with deviations or perforation may be more effective with designed 3D printed access guides that seems to be a safe and clinically feasible method to locate root canals.